Accesibilidad espacial e inclusión social: experiencias de ciudades incluyentes en Europa y Latinoamérica. (2018)
This dissertation considers spatial accessibility as the first element to reach the social inclusion of people with disabilities. For this purpose, it was inquired about what are the strategies used by governments to overcome the social exclusion of this human group to the physical environment? And how do the strategies of Latin America and Europe differ? A documentary research is carried out, generating a dialogue between twenty-three sources. As findings, we can highlight the consolidation of a common bet pushed by social movements around public space, transport, built environment, information and ICT, social services, equipment; as well as the approval of circumstantial laws in Latin America that revolve mainly around transport and associated infrastructure. This is how, despite the asymmetries, there is greater awareness about the social inclusion of this population group in the planning and territorial development processes.